Role of Apoptosis in the Pathogenesis of Common Variable Immunodeficiency (CVID) - Ganjalikhani-Hakemi, Mazdak; Yazdani, Reza; Esmaeili, Mohammad; Abolhassani, Hassan; Rae, Wiliam; Azizi, Gholamreza; dizaji, Majid Z.; Shaghaghi, Mohammadreza; Rezaei, Abbas; Abbasi-Rad, Faezeh; Afshar-Qasemloo, Sanaz; Mohammadi, Saeed; et al. (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2017)
Background: Common variable immunodeficiency (CVID) is a heterogeneous immune deficiency characterized by hypogammaglobulinemia. Since B cell maturation and differentiation is defective in this disorder, we evaluated apoptosis in B cells of patients with CVID compared with healthy donors (HD). Methods: Determination of peripheral blood B-cell subsets in CVID and HDs, was performed using flow cytometry. We compared total apoptosis, early apoptosis and late apoptosis/necrosis in unstimulated and stimulated B-cells of patients with CVID and HDs. We also assessed the expression of the anti-apoptotic molecule BCL2 mRNA levels in B-cells by real-time PCR in CVID patients compared with HDs. Results: Total B-cell apoptosis was increased in both unstimulated and stimulated B-cells from CVID patients compared with HDs (p=0.02 and p=0.004). Early apoptosis in stimulated B-cells (p=0.04) and late apoptosis/necrosis of B-cells in both unstimulated and stimulated B-cells (p=0.04 and p=0.03, respectively) were significantly higher in CVID patients compared with HDs. There was a significant inverse correlation between the percentages of post germinal center B-cells in the peripheral blood of CVID patients compared with percentage of apoptotic B-cells. However, anti-apoptotic BCL2 expression was not significantly reduced in B-cells from CVID patients compared with HDs (p=0.16). Conclusion: Increased apoptosis of B-cells may be a factor in abnormality of differentiated B-cell subsets and the impaired endogenous immunoglobulin production in CVID patients. Further studies of the expression of pro/anti-apoptotic mediators in B-cells of CVID patients may shed light on the mechanism behind this increased B-cell apoptosis, and present potential therapeutic interventions in the future.
Keywords: B cell subsets